Strategi Guru BK Dalam Meningkatkan Kedisiplinan Siswa Di SMA N 1 Tanjung Mutiara - Eldina Fitri; Yeni Afrida (Universitas Maritim AMNI Semarang, 2024)
This research was conducted at SMA N 1 Tanjung Mutiara, an educational institution where there is a lack of student discipline regarding school regulations such as being late for class, non-compliance with dress codes, and absenteeism in lessons so that many teachers complain about this phenomenon that occurs among students. Therefore, guidance and counseling teachers play a very important role in dealing with students who show behavior that lacks discipline. Existing research problems relate to the effectiveness of strategies in improving student discipline. The aim of this research is to find out what strategies will be implemented by guidance and counseling teachers to improve student discipline. The informants for this research consisted of BK teachers at SMA N 1 Tanjung Mutiara who took part in the interviews. This research uses qualitative methodology. It was found in this research that guidance and counseling teachers use an individual counseling approach, especially in the form of personal counseling between students and guidance and counseling teachers. The goal of individual counseling is to assist students in changing their attitudes and behavior so that they can more effectively adapt to the school environment and fulfill their responsibilities as conscientious members of student groups.